2000
DOI: 10.1093/jn/130.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Magnesium Supplementation Affects Bone Metabolism and Dynamic Strength of Bone in Ovariectomized Rats

Abstract: We evaluated the effect of magnesium supplementation on apparent calcium absorption, bone metabolism and dynamic bone strength in ovariectomized (OVX) rats as a model of postmenopausal women. Two groups of OVX rats were fed a 0.05% Mg diet or a 0.15% Mg diet, and one group of sham-operated rats was fed the 0.05% Mg diet for 42 d. We collected feces and urine of all rats for 3-d periods starting from d 3, 10, 17, 24, 31 and 38 of the feeding experiment for calcium and magnesium balance studies. Urine was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 24 publications
3
55
0
2
Order By: Relevance
“…In addition, previous reports have shown that bone quality deteriorates under a low Mg condition [14,15], and that subjects at low serum Mg levels are at risk for bone fractures [12]. It has been reported that dietary Mg supplementation affected bone metabolism and dynamic strength of bone in ovariectomized rats [16]. Family members affected with primary hypomagnesemia due to renal Mg wasting inherited in an autosomal dominant manner have been reported to demonstrate significant reductions in serum and lymphocyte Mg concentrations as well as decreased BMD values at the lumbar spine and proximal femur [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous reports have shown that bone quality deteriorates under a low Mg condition [14,15], and that subjects at low serum Mg levels are at risk for bone fractures [12]. It has been reported that dietary Mg supplementation affected bone metabolism and dynamic strength of bone in ovariectomized rats [16]. Family members affected with primary hypomagnesemia due to renal Mg wasting inherited in an autosomal dominant manner have been reported to demonstrate significant reductions in serum and lymphocyte Mg concentrations as well as decreased BMD values at the lumbar spine and proximal femur [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mg deficiency could inhibit the synthesis of 1,25-dihydroxy vitamin D (1,25(OH) 2 D) [9][10][11] as well as its action on bone [11]. Accumulating data have shown that a long-term Mg deficiency and resulting hypomagnesemia could cause osteoporosis and bone fractures through these dysfunctions of PTH and vitamin D action [12,[13][14][15][16][17][18][19]. However, other studies have shown no relationship between Mg deficiency and osteoporosis [20][21][22], and it still seems to be controversial whether or not Mg deficiency could cause osteoporosis.…”
mentioning
confidence: 99%
“…Toba et al (1999) reported that when doi: 10.17221/3/2016-CJAS growing male rats were fed three times more Mg compared to the control group, an increase in bone-breaking energy was observed. Toba et al (2000) also reported that Mg supplementation in ovariectomized rats promoted bone formation by activating osteoclasts. High Mg supplementation may cause laxative problems.…”
Section: Introductionmentioning
confidence: 91%
“…Similarly, Toba et al showed that magnesium supplementation promotes bone formation (increases in osteocalcin) and prevents bone resorption (decreases in deoxypyridinoline and parathyroid hormone). 13 They also found a reduction in calcium adsorption, which supports the decrease in bone resorption since lower levels of serum calcium stimulate the release of parathyroid hormone. 13 Given that magnesium is a mineral essential for bone growth, it can be expected that as a biomaterial it would support bone growth.…”
Section: Introductionmentioning
confidence: 82%